Community Technical Support for Rebuilding After Cianjur Landslides Due to Earthquake 2022 - Hutabarat, Lolom Evalita; Simanjuntak, Pinondang; Tambunan, Efendy; Christianti, Candra (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
The occurrence of earthquake disasters in Indonesia, attributed to its location within the Ring of Fire, consistently leads to human and material losses for the residents residing in the impacted areas. The seismic event on November 21, 2022, at Cianjur, resulted from tectonic activity along the Cugenang Cianjur fault and subsequent landslides near Sarampad Village, the horseshoe-shaped region. The seismic activity associated with an earthquake can induce landslides, amplifying their destructive potential and posing a severe threat to slopes already susceptible to instability. Still, landslides can occur for various reasons depending on the local soil and weather. Subsequently, a data collection process was undertaken to allocate governmental aid to the community to reconstruct their residences. The Cugenang fault area is characterized by its topographical features, including mountain slopes, hillsides, and river cliffs or valleys. Specifically, areas with slopes over 40% are classified as zone A. The identification of landslide-prone locations is conducted following established protocols such as Landslide Management Planning Procedures SNI 03-1962-1990, Field Engineering Geological Mapping Procedures SNI 03-2849-1992, and Procedures for Making Slope Maps SNI 03-3977-1995. If necessary, community mitigation actions can be implemented after identifying landslide danger or regions at risk. In the event of a landslide, communities employ several methods, including preparation, engineering, acceptance, and monitoring and warning systems. Planning control reduces risk; an engineering solution strategy reduces landslide probability or impact. Acceptance strategy accepts or unavoidable, and monitoring and warning system strategy reduces risk by evacuating before failure